A comparative study of child witness between Islamic and civil law in Malaysia / Muliani Asari…[et al.] - Asari, Muliani; Husain, Norhakimah; Rusli, Norharniza; Ahmad Sukri, Nurul Shashabilla (2009)
This research provides a comparative approach to child witness in Islamic Law and Civil Law in Malaysia. This research comprises of six chapters, where chapter 3 to 6 are the most important contents in the research. The information on child witness in Islamic and Civil Law has been stipulated in different chapters, so that the readers can clearly understand. The core of the research is in chapter 5 where all the comparison of child witness in Islamic Law and Civil Law can be found There are 5 comparisons found between Islamic Law and Civil Law based on the materials and sources during the research was conducted. The comparison had been made between the definitions of child witness, the age of the minor, competency of child witness, the procedures involved in examining the child witness and also the acceptance of child witness in these both laws. This research ended with the recommendation that had been discussed in chapter 6. Here, some recommendations were made based on the defect that had been found which are in the scope of the provision, Acts and administration of the court regarding the child witness. This research attempts to cover all the matters and issties involving the dispute in accepting the child as a witness as an important evidence in court including Syariah and Civil Court.